An investigation of crystallization kinetics of polyoxymethylene in processing conditions. (1st November 2022) - Volpe, Valentina; Speranza, Vito; Schrank, Theresia; Berer, Michael; Pantani, Roberto
Abstract: In this work, a very wide set of quiescent isothermal and non‐isothermal calorimetric experiments are carried out in order to analyze POM crystallization kinetics also under cooling rates comparable to those experienced by the polymer during processing. To investigate the effect of flow on the POM crystallization behavior, also some Linkam shearing tests are conducted. An enhancement of the POM crystallization process is observed under flow. A Kolmogoroff–Avrami–Evans (KAE) model for quiescent crystallization is proposed. It is based on nucleation (considering both a homogeneous and a heterogeneous process) and growth mechanisms. Model parameters of nucleation and growth are determined, and the overall model is able to describe the POM crystallization process in the whole cooling rate range adopted for the experiments. This allows to obtain a reliable description of the POM crystallization evolution during processing and provides important knowledge for managing the POM injection molding process and the final physical properties of POM products.